Electrochemical Studies on Interaction of Ofloxacin with ITO-PANI Supported Bilayer Lipid Membrane - Poornima, K.; Periasamy, M.; Rameshkumar, S.; Sankar, A. (International Journal of Membrane Science and Technology, 2023)
Bilayer phospholipid membrane was formed on the ITO-Pani surface in NaCl bath solution at different pH. Characterization and interaction of bilayer lipid membrane (BLM) with Ofloxacin molecules in 0.1 M NaCl solution was studied at different pH employing electrochemical impedance spectroscopy, cyclic voltammetry and chronoamperometric methods. The changes in the properties of BLM due to addition of Ofloxacin depends on the pH of bath solution. At low pH the membrane surface is positively charged and the interaction of drug molecules with the BLM surface takes place through chloride bridge. At alkaline pH the membrane surface is negatively charged and the drug molecules get attached through hydrogen bonding. The results of electrochemical impedance spectroscopy, cyclic voltammetry and chronoamperometry support each other.